Efeitos do ácido α-lipóico nas alterações comportamentais e neuroquímicas induzidas pela administração de solifenacina - Dantas, Leonardo Pimentel (2023)
Recent epidemiological studies have demonstrated adverse effects of bladder antimuscarinics such as solifenacin (Sol) on cognitive function and risk of dementia. The pathophysiology observed in cases of dementia, especially in Alzheimer's disease, may be related to neuroinflammation and oxidative stress. In this context, α-lipoic acid (ALA), due to its antioxidant, anti-inflammatory and neuroprotective potential, was used in this research with the objective of trying to reduce the behavioral and neurochemical effects induced by the cumulative use of the antimuscarinic Sol. The presentation of this thesis was divided into 2 scientific articles (2 chapters), the first being a scientific review demonstrating and discussing the effects of Sol on memory and the second, where the effects of Sol alone or associated with ALA on behavioral memory tests and their relationship with nitro-oxidative stress were studied. Mice in the control group received saline solution for 14 or 28 days. The groups treated only with Sol received daily doses (1 or 2 mg/kg, orally) of this drug for 14 or 28 days. The three groups treated with ALA (200mg/kg) received: a) saline solution for 14 days + ALA from the 15th to the 28th days, b) Sol for 14 days and Sol + ALA from the 15th to the 28th days or c) Sol + ALA for 28 days. Behavioral tests were performed and determined the nitro-oxidative changes and acetylcholinesterase activity in the prefrontal cortex (PFC), hippocampus (HC), and striatum (ST). IL-1 and TNF- levels in HC were also determined. Sol produced memory alterations in mice, reducing the descent latency time in the passive avoidance test and the recognition index in the novel object recognition test. Sol also increased lipid peroxidation in PFC, HC, and ST and nitrite levels in HC. On the other hand, ALA associated with Sol was able to reduce the effects caused by the Sol alone, both in relation to the nitro-oxidative parameters and in relation to the behavioral tests, also decreasing the acetylcholinesterase activity in the HC. There was no significant change in IL-1 and TNF- levels in HC. These results suggest that the behavioral changes induced by Sol involve nitro-oxidative mechanisms, opening perspectives for the use of ALA as a neuroprotective adjuvant drug in patients who need prolonged use of Sol.